The Conspiracy of the Miscellaneous in Foucault's Pendulum - Ken Kirkpatrick (Studies in 20th & 21st Century Literature, 1995)
Like Name of the Rose, Foucault 's Pendulum grows out of and comments on Umberto Eco's theoretical work. Eco's decision to turn to a conspiracy, rather than a straight detective format for his second novel fits with his recent concern about how interpretative communities function in a period of divisive, diffuse critical theory. Yet Foucault's Pendulum does not merely amplify or dramatize his position; rather, it undermines it by becoming excessively involved in generating conspiracy. It is a satire in which the thing satirized proves more interesting and engaging than the satirical position. Nevertheless, Eco does raise concerns about the conspiratorial, especially the way in which it invalidates ironic detachment and solidarity at the same time, making conspirators inevitable victims of their own conspiracy. And he suggests an important extension of the relation between signs and interpretation: if the detective novel, like Name of the Rose, deals with the special referentiality of signs as clues, the conspiratorial novel, like Foucault's Pendulum, deals with the "paranoid" side of unlimited interpretation—the possibility that every sign, not arbitrarily but capriciously, can reveal an excess of design.
Keywords: Foucault' s Pendulum; Umberto Eco; novel; interpretive communities; critical theory; conspiracy; detective novel; signs